Analyzing Spatial Deixis in The Film Raya and The Last Dragon (2021) - Riska Nurjanah Daeng Sita; Suleman Bouti; Rahman Taufiqrianti Dako (Kirana Publisher (KNPub), 2026)
This study analyzes spatial deixis in the animated film Raya and the Last Dragon (2021) using a pragmatic approach. The study aims to answer the research question what types and function of spatial deixis are found in the dialogues of the film Raya and The Last Dragon (2021). The theoretical framework applied in this study draws on Levinson's (1983) and Yule's (1996) proximal-distal classification for identifying types of spatial deixis, and Fillmore's (1997) gestural-symbolic distinction for analyzing their communicative functions. This study employs a descriptive qualitative research design. The data consist of verbal utterances containing spatial deictic expressions produced by the characters throughout the film, collected through repeated observation of the film and verification using the official screenplay. The data were analyzed through a four-stage procedure consisting of code development, data classification, interpretation, and drawing conclusions. The findings reveal that 20 instances of spatial deixis were identified, consisting of 11 instances of proximal spatial deixis and 9 instances of distal spatial deixis. In terms of function, 12 instances were classified as symbolic use and 8 instances as gestural use. Both functions were found to occur across both types, confirming that type and function are independent dimensions of deictic analysis. The findings demonstrate that spatial deixis in the film operates through both the speaker's immediate physical relationship to the referent and the shared situational knowledge of the communicative context, with the multimodal character of animated film playing a decisive role in enabling gestural deictic reference.